PENDIDIKAN KEIMANAN ANAK DALAM KELUARGA MENURUT ZAKIAH DARADJAT - Muslimawaty, Rivanti (Prodi PAI IAILM Suryalaya, 2018)
Many parents do not understand the concept of faith education inchildren. This could be based on an assumption that children are stilltoo young to be educated in matters of faith. Whereas the family, in thiscase the parents, is an educational institution that is directly related tothe child since he was born. So there is a thought that the family isbelieved to have a very strong influence on children’s religiouseducation. This happens because the relationship that exists betweenparents and children for 24 hours is very important in education.Zakiah Daradjat is an education expert who also believes that theimportance of faith education is given to children as early as possible,so the purpose of this study is to find out how Zakiah Daradjat’sthoughts about children’s religious education are in the family. Byusing qualitative research methods, the author seeks to explain theeducation of children’s faith in the family according to ZakiahDaradjat. The author found that Zakiah Daradjat had clear thoughtsabout children’s religious education in the family, which aims to makechildren as human beings, through the six pillars of faith, with methodsof exemplification, habituation, wrong correction, erroneous quarrelsthat occur and reminding the forgotten. The evaluations carried out inthe form of memorization tests, tests of understanding and practice ofworship. This makes Zakiah Daradjat’s thoughts still relevant to beapplied in today’s life and become a reference for psrents, teachers abdother related parties.